Modern State And Problems Of Preparing Future Engineers For Such Activities - Nosirov Jakhongir Normurod o‘g‘li (Genius Journals, 2024)
This work reflects on the current situation and problems of training future engineers in higher education institutions
Keywords: engineer; knowledge; skills; professional competence